The effects of respiratory muscle training on VO2max, the ventilatory threshold and pulmonary function - Amonette, W. E.; Dupler, T. L. (Journal of Exercise Physiology online, 2002)
This study evaluated the effect of inspiratory and expiratory muscle training on pulmonary function and maximal exercise performance in competitive triathletes and marathon runners. The participants in this study (N=12) had a mean weekly aerobic training time of 7.5 hours per week of swimming, cycling, or running. Eight subjects were assigned to a pulmonary resistance treatment group and four control subjects were given a sham device that allowed no greater than 15% resistance on inspiration or expiration. The subjects performed 30 maximal inhalation/exhalation maneuvers on their respective devices two times per day for four weeks. The subjects were tested for forced vital capacity (FVC), forced expiratory volume in one second (FEV1), FEV1/FVC ratio, forced inspiratory vital capacity (FIVC), peak inspiratory flow rate (PIFR), and peak expiratory flow rate (PEFR). Each subject was also tested for peak exhalation force (PEF) as well as a maximal oxygen consumption (VO2 max), carbon dioxide production (VCO2), tidal volume (VT), ventilation (VE), ventilatory threshold (VT), and respiration rate (RR). The data revealed that training using the pulmonary resistance device produced significant increases in maximal VE and maximal VT while decreasing RR (although not statistically significant) at maximum exercise. However, no significant changes were seen in VO2 or any pulmonary function variables measured. ABSTRACT FROM AUTHOR